Acupuncture Reduces the Risk of Dysphagia in Stroke Patients: A Propensity Score-Matched Cohort Study - Qiu, Xuan; Yao, Xiao-Jie; Han, Sheng-Nan; Wu, Yun-Yun; Ou, Zeng-Jian; Li, Tian-Shi; Zhang, Hong (Frontiers in Neuroscience, 2022)
Background: Post-stroke dysphagia (PSD) affects the quality of life in stroke patients, impairs their rehabilitation ability, and induces other complications following stroke. There is currently some understanding of PSD risk factors, but its protective factors remain largely unknown. Objective: This article aimed to analyze the effects of acupuncture (AP) on dysphagia in stroke patients and explore its potential as a preventive therapy. Methods: Patients who had a diagnosis of stroke from 2010 to 2019 were selected and followed until 2020, utilizing factors such as age, gender, stroke location, stroke type, and baseline comorbidity. To compare the incidence of dysphagia, equal numbers of stroke patients treated with and without AP (n=1,809) were matched with 1:1 propensity score. The Cox proportional hazards model and Kaplan-Meier approach were employed to assess the risk of dysphagia as an outcome measure. Results: The stroke patients treated with AP had a lower risk of dysphagia after adjusting for age, gender, stroke location, stroke type, and baseline comorbidity [adjusted hazard ratio (AHR)=0.43, 95% confidential interval=0.37-0.49] compared with those in non-AP cohort. AP also decreased the risk of PSD among different gender groups. The risk ratios were AHR=0.45 and AHR=0.33 for males and females, respectively. AP also reduced the risk for PSD among different age groups. The risk ratios were AHR=0.20, AHR=0.37, AHR=0.41 and AHR=0.45 for the 18-39, 40-59, 60-79 and >80 years old groups. With regard to stroke types (ischemic, hemorrhagic and mixed type), patients treated with AP had a lower risk (AHR=0.47, 0.28 and 0.17, respectively). With respect to stroke location, whether it was the brain stem (AHR=0.41), diencephalon (AHR=0.13), and multiple lesions (AHR=0.40), the risk of PSD in AP-treated patients was decreased. For all baseline comorbidities, AP attenuated the risk of dysphagia. The cumulative incidence of dysphagia was remarkably lowere in AP group than in non-AP group (log-rank test, P=0.000). Conclusion: AP treatment attenuates the risk of dysphagia in stroke patients. Future research should increase the sample size and further elaborate on the details of AP protocol.